Propagation models and their effect on the congestion control in vehicular ad hoc network. (12th March 2021) - Sharma, Swati; Harit, Sandeep
Vehicular networks form a growing field of wireless technology that pays attention to a wide range of applications, from infotainment to safety applications. One of the most vital challenges faced by vehicular ad hoc network (VANET) is to choose an appropriate propagation model providing accurate and realistic propagation details. In VANET, the realistic propagation model requires mobility, detail of vehicles, network topology, and information of message dissemination. Although all the vehicles are sharing the same limited bandwidth, an increase in vehicle density results in congestion in the network, leading to packet loss and delay in the delivery of messages. Therefore, it is necessary to control the congestion for the high performance of the vehicular network. This paper illustrates various propagation mechanisms and effects on wireless propagation. Further, the classification of different propagation models is discussed, along with their mathematical expressions. Finally, we provide an overview and taxonomy of several VANET-specific propagation models with their impact on the decentralised congestion control (DCC) algorithm through simulation. This paper's objective is to classify the propagation models and provide researchers with the guidelines to understand the effect of propagation models on the DCC algorithm.